Major depressive disorder and impaired health‐related quality of life among US older adults. (19th July 2020) - Rhee, Taeho Greg; Steffens, David C.
Abstract : Objectives: To examine the association of current and past major depressive disorder (MDD) and measures of health‐related quality of life (HRQOL) in a nationally representative sample of older adults. Methods: Cross‐sectional analysis of the 2012 to 2013 National Epidemiological Survey on Alcohol and Related Conditions Wave III (NESARC‐III) was used. NESARC‐III is a nationally representative health interview survey on substance use and mental health in the US, and we limited our sample to survey respondents aged 65 or older (n = 5806 unweighted). Using DSM‐5 criteria, we identified older adults with current MDD, past MDD (ie, prior but not current MDD), and no history of MDD. Using standardized algorithms, we also constructed HRQOL measures: mental component summary (MCS), physical component summary (PCS), and quality‐adjusted life years (QALYs). We performed multivariable‐adjusted linear regression analyzes to assess the associations of MDD types with HRQOL measures while adjusting for socio‐demographics and clinical co‐morbidities. Results: Overall, 14.4% of the older adults, representative of 6.0 million nationwide, met criteria for lifetime MDD. About 2.2 million older adults (5.4%) had current MDD and 3.7 million older adults (9.0%) had past MDD. Older adults with current or past MDD had a moderate difference in HRQOL measures compared with never depressed (Cohen's d measures ranging from −1.02 to −0.07). When controlling for other covariates, MCS and QALYs measures were lowest in the current MDD group. Conclusion: Current MDD is associated with significantly lower HRQOL than never MDD, while adults with past MDD had minor (often insignificant) residual impairment in HRQOL.